Breakfast on Pluto - McCabe P. Patrick (London, Picador, 1999)
From internationally acclaimed author Patrick McCabe, the Booker Prize-nominated novel that tracks the chaotic life of an abandoned orphan who becomes a transvestite and braves the combustible streets of London in the 1970s.